Evaluation of a diagnostic device, CL Detect rapid test for the diagnosis of new world cutaneous leishmaniasis in Peru. - Max Grogl; Christie A Joya; Maria Saenz; Ana Quispe; Luis Angel Rosales; Rocio Del Pilar Santos; Maxy B De Los Santos; Ngami Donovan; Janet H Ransom; Ana Ramos; Elmer Llanos Cuentas (Public Library of Science (PLoS), 2023)
Background Cutaneous leishmaniasis (CL) is a neglected disease and a public health problem in Latin America. The diagnosis of CL in poor hyperendemic regions relies to large extent on the identification of amastigotes in Giemsa-stained smears. There is an urgent need for a rapid, sensitive and low cost diagnostic method for use in field conditions for CL as current modalities are not readily available. The primary objective of this study was to determine the sensitivity and specificity of the FDA-cleared CL Detect Rapid Test in Peru, using modified test procedures rather than the instructions-for-use, by 1) increasing the extraction time and 2) increasing the volume of the sample added to the test strip. CL Detect Rapid Test results were compared against microscopy and kDNA-PCR, for the diagnosis of CL in ulcerated lesions. In addition, we compared two collection methods the dental broach used and mentioned in the CL Detect insert and the standard less invasive and easier to conduct scrapping method. Methodology Participants were patients who presented for medical consultation due to a suspected CL lesion. Four samples from the index lesion were collected using a dental broach, per package insert, and lancet scraping and tested by the modified CL Detect Rapid Test, microscopy, and PCR. Principal findings A total of 156 subjects were eligible and evaluated. The modified CL Detect sensitivity was higher in specimens obtained by scraping (83.3%) than those from dental broach (64.2%). The specificity was lower in scrapings (77.8%) with a false positive rate of 22.2% compared with dental broach samples (91.7%) with a false positive rate of 8.3%. However, molecular analysis showed that all 8 false negative microscopy scrapings (those positive by modified CL Detect and negative by microscopy) were positive by kDNA-PCR, meaning that the modified CL Detect was more sensitive than microscopy. Conclusions These modifications to the package insert that resulted in a diagnostic sensitivity (83.3%) comparable to microscopy for species found in Peru may enable earlier anti-leishmanial drug treatment decisions based on a positive result from the CL Detect Rapid Test alone until further diagnostic tests like microscopy and PCR can be performed. Trial registration NCT03762070; Clinicaltrials.gov.